Struktutr Komunitas Ikan dan Tutupan Karang di Area Biorock Desa Pemuteran, Buleleng, Bali - Arifin, Febriyanto; Dirgayusa, I Gusti Ngurah Putra; Faiqoh, Elok (Journal of Marine and Aquatic Sciences; Vol 3 No 1 (2017), 2017)
Biorock is new method of coral reef rehabilitation. Today, the structure Biorock been made in various shapes and sizes. Therefore, assessment of reef fish communities and coral cover on the artificial reef Biorock of different sizes are needed as a as the basic information and the utilization of the results of the conservation area. From this research, it is known that the six Biorock structure obtained reef fish composition consisting of 18 Family and 45 fish species and abundance of total 2065 individuals. In accordance with the classification of diversity index Shannon - wiener all sizes Biorock the research object falls into the range of values diversity moderately 1.57 - 2.95. The results of the uniformity index show that in every size Biorock has equal distribution of species. From the results of the dominance of index calculation (C) is included in the low category. Where in any size Biorock not happen domination by a single species. In all sizes Biorock have value mengindikasinkan that coral is in good shape. The highest coral cover in sequence contained in the structure of Small-sized Biorock 1, 1 medium, 2 Large, 2 Small, 2 Medium, and 1 Large. From analysis using Bray-Curtis similarity index gained 2 groups Biorock structures that have similar types of fish encountered. The first group is the first Large-sized Biorock structure, Large 2, and the medium 1. The second group is the structure of Small-sized Biorock 1, 2 medium and 2 Small.
Keywords: Biorock; community structure,coral cover; Bray-Curtis Similarity Index